Qualitative gender analysis country report, Cameroon: Building equitable climate resilient African bean and insect sectors - Siri, Bella Ngoh; Munji, Victorine; Ntam, Fidelis; Mafouasson, Hortense; Lutomia, Cosmas; Ouya, Frederick; Ketema, Dessalegn; Nchanji, Eileen (2025)
The report presents findings and recommendations from a qualitative study conducted in three regions of Cameroon: West, Adamawa, and Southwest. The study is part of the Building Equitable Climate Resilient Africa Bean & Insect (BRAINS) baseline study in Cameroon. The BRAINS project aims to enhance equitable climate resilience to improve food and nutrition security in Sub-Saharan Africa (SSA) through gender-responsive interventions in common bean, insect, and fruit tree value chains. The study collected data through focus group discussions, key informant interviews, and in-depth interviews with farmers, entrepreneurs, persons living with disabilities, and other marginalised groups. The study finds distinct gender and age-related roles associated with traditional and gender norms in the common bean, insect, and fruit tree value chains across the studied regions. These roles influenced gender division and power relations within households. In the common bean value chain, older men typically engage in land preparation, chemical application, and marketing. In contrast, older women are more involved in planting, harvesting, and selling beans in local markets. Young household members, especially men, engage in physically demanding tasks such as land preparation and harvesting. Men dominate initial farming activities in the fruit value chain, such as nursery preparation and transplanting. They are also involved in chemical applications. In contrast, women are more involved in the field maintenance of fruit trees and the marketing of fruit produce. Young men assist with labour-intensive activities, while young women engage in processing and marketing. Unlike common bean farming and marketing, beekeeping and insect farming are male-dominated value chains. Men and male youth are involved in hive construction, installation, and honey harvesting. Women and young women are only involved in processing honey into various products and in marketing. Climate change is posing challenges to common bean production, beekeeping, and fruit tree farming, affecting the livelihoods of women and men across all regions. Farmers across the identified areas identified droughts, heavy rains, pest infestations, changes in rainfall patterns, and rising temperatures as the most critical climate change phenomena that significantly impact common bean, fruit tree, and bee value chains. While these changes worsen the already challenging welfare and farming challenges experienced by PLWD, they also burden women by increasing their workload and reducing their decision-making power within households. Despite the adverse effects of climate change, the adoption of climate resilience practices is relatively low, especially among PLWD and farmers engaged in beekeeping and fruit tree value chains. Furthermore, support for climate resilience from NGOs and government initiatives is low, despite farmers belonging to and acknowledging the importance of collective action and social networks. Adoption of carbon-reducing waste management practices is low. Specifically, PLWD and other marginalised groups do not engage in waste management practices. Furthermore, waste management practices varied and showed seasonal variations. Women and youth are primarily responsible for managing household and agricultural waste. The findings emphasise the critical importance of understanding gender roles and decision-making, climate change impacts, the role of social networks, waste management practices, access to financial services, and the potential for business growth across Cameroon’s four value chains. These results have both policy and practice implications that could be addressed by considering the recommendations that aim to improve resilience, productivity, and inclusivity in the fruit tree, common bean, and bee value chain in Cameroon: • Enhancing information sharing on climate-resilient practices • Promoting gender inclusivity in the three value chains. • Supporting development of value-added products across the value chains • Education and awareness creation in waste management for efficient waste management practices. • Formation and strengthening of social networks. • Fostering collaboration and collective action. • Gender transformative approaches to shift harmful gender norms.